A crystal engineering approach for the design of multicomponent crystals and assembly of nano-scale architectures - Hurley, Evan Patrick (Kansas State University, 2013)
The work presented in this thesis has demonstrated that supramolecular synthons can be used to make multicomponent crystals, and various synthons can be combined to make supermolecules. The synthons can also be used to construct nanoscale assemblies. Molecules containing single and multiple hydrogen-bond (HB) and halogen-bond (XB) acceptor sites have been synthesized in an effort to carry out supramolecular synthesis in order to establish a reliable hierarchy for intermolecular interactions. Pyrazole-based molecules have been made, combined with various carboxylic acids, and characterized using infrared (IR) spectroscopy to give a success rate of 55-70%. Reactions that gave a positive result were converted to solution experiments, and crystals were grown and characterized using single-crystal X-ray diffraction (XRD). The co-crystals display infinite 1-D chains with the intended stoichiometry and structural landscape on 6/6 occasions. The salts, on the other hand, display unpredictable stoichiometry and structural landscape on 5/5 occasions. Furthermore, the electrostatic charge on the primary hydrogen-bond acceptor, N(pyz), can be altered by adding a nitro, R-NO2, covalent handle to the backbone of the pyrazole molecule. Addition of a strongly electron withdrawing group significantly lowered the charge on the pyrazole nitrogen atom and, in turn, lowered the supramolecular yield to 10%. Ditopic molecules containing pyrazole and pyridine on the same molecular backbone were synthesized and characterized using 1H NMR. The molecules were co-crystallized with carboxylic acids, and the resulting solids were characterized using IR spectroscopy. The solids could then be classified as co-crystal or salt using specific markers in the IR spectrum. Single-crystal XRD was used to observe the intermolecular interactions in the co-crystals and salts, and the co-crystals were assigned to two groups: Group 1 (2) and Group 2 (2). The salts (4) show more unpredictability with stoichiometry and structural landscape. A library of ditopic molecules containing triazole and pyridine acceptor sites were synthesized and characterized using 1H and 13C NMR. The molecules were co-crystallized with carboxylic acids and the resulting solids were characterized using IR spectroscopy which demonstrated a 100% supramolecular yield whenever a pyridine moiety was present, consistent with results from Chapter 3. Single-crystal XRD was used to identify the intermolecular interactions in the co-crystals (2) and salt (1), and the results show that triazole can compete with pyridine for hydrogen bond donors. A library of ditopic molecules was also used for halogen-bonding (XB) studies with a series of activated iodine and bromine-based donors. The results show that iodine donors have a higher success rate range (12.5-75%) compared to bromine donors (16.7-50%) based on results obtained from IR spectra. Furthermore, the results from the XRD show that pyrazole nitrogen atoms can compete with pyridine for forming XB, and two groups of supramolecular synthons were observed. Finally, relatively weak non-covalent interactions, HB and XB, can influence the assembly of nanoparticles based on IR spectroscopy and TEM images. The assembly of the particles is influenced by specific capping ligands, which were synthesized and characterized using 1H, 13C and 19F NMR. The results demonstrate that relatively weak non-covalent interactions based on HB and XB interactions can influence nanoparticle assembly.
Keywords: Crystal Engineering; Nanoscale; Chemistry (0485)